Эхо чужих грехов: [роман] / Марта Таро - Таро Марта (Галантный детектив, 2017)
Экземпляры: СБ (20170703) / Инвентарный номер: 54150 / Цена: 224.00 / Сис.шифр: Р2 / Авт.знак: Т 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6